Cistrome Data Browser: expanded datasets and new tools for gene regulatory analysis. Issue Volume 47:Issue D1(2019) (20th November 2018) - Zheng, Rongbin; Wan, Changxin; Mei, Shenglin; Qin, Qian; Wu, Qiu; Sun, Hanfei; Chen, Chen-Hao; Brown, Myles; Zhang, Xiaoyan; Meyer, Clifford A; Liu, X Shirley
Abstract: The Cistrome Data Browser (DB) is a resource of human and mouse cis-regulatory information derived from ChIP-seq, DNase-seq and ATAC-seq chromatin profiling assays, which map the genome-wide locations of transcription factor binding sites, histone post-translational modifications and regions of chromatin accessible to endonuclease activity. Currently, the Cistrome DB contains approximately 47, 000 human and mouse samples with about 24, 000 newly collected datasets compared to the previous release two years ago. Furthermore, the Cistrome DB has a new Toolkit module with several features that allow users to better utilize the large-scale ChIP-seq, DNase-seq, and ATAC-seq data. First, users can query the factors which are likely to regulate a specific gene of interest. Second, the Cistrome DB Toolkit facilitates searches for factor binding, histone modifications, and chromatin accessibility in any given genomic interval shorter than 2Mb. Third, the Toolkit can determine the most similar ChIP-seq, DNase-seq, and ATAC-seq samples in terms of genomic interval overlaps with user-provided genomic interval sets. The Cistrome DB is a user-friendly, up-to-date, and well maintained resource, and the new tools will greatly benefit the biomedical research community. The database is freely available athttp://cistrome.org/db, and the Toolkit is athttp://dbtoolkit.cistrome.org .